Corruption: Is it a Moral Issue or a Legal Issue? - Pelengkahu, Muhamad (Corruptio, 2024)
The objective of this research is to examine the discourse surrounding corruption, with a particular focus on whether it is perceived as a legal issue or a moral issue. This research was conducted in response to the shortcomings of scholars' analysis in discussing the issue of corruption. Furthermore, in light of the considerable number of corruption cases globally, particularly in Indonesia, it is imperative that the government and relevant stakeholders reframe corruption as a national concern. This research is a descriptive qualitative study, employing data collection techniques through literature studies and analysis using deductive syllogism tools. The research concluded that corruption has become a social disease that continues to spread from upstream to downstream of human life. Currently, corruption is only focused on legal reform, whereas the root or heart of corruption is morality. Corruption is a moral issue, not a legal issue; therefore, it must be addressed through a moral, ethical, and transcendental approach.